STRATEGI PEMASARAN PRODUK RANGKA ATAP BAJA RINGAN PADA PT. HARI REZEKI KITA SEMUA PEKANBARU - Sintia Dewi Pratiwi; Lilis Suriani (VALUTA, 2017)
Basically consumer decisions to buy and consume a particular product is strongly influenced by the quality of existing products in the product, because it is impossible for a consumer to buy a product without knowing the superiority of the product. The quality of products that affect consumers in making decisions is very important because it is useful to put interest and taste. Besides, it is necessary to make some improvements to the quality of products produced such as: improving product quality in terms of brand, ease of getting product, service, responsibility, and product completion time. This is important to expand market share and to keep the company retained its customers. This is what makes researchers interested to see the relationship between product quality and purchasing decisions, because with the existence of Product Quality Analysis done conceptually by industry can influence consumer purchasing decision to a product. Type of research used is descriptive research type. This type of descriptive research is a study done with the main purpose to provide a description or description of a situation objectively. For example, observing consumer purchasing decision on light steel roof truss product of Prima Truss at PT. Hari Rezeki Kita Semua Pekanbaru. The research sample is 1 person Head Production, 1 person leadership, and 30 consumers. types and techniques of data collection used consisted of primary data obtained directly from the respondents by using questionnaire and interview techniques and secondary data collected by means of observation. While the data analysis technique used is by descriptive method. Based on analytical techniques, the researchers assessed and concluded that the Quality Analysis of Light Steel Frame Roof Products was in the category of Good Enough. Recommendation to be considered is the company should further improve the quality of Prima Truss products, especially those that include performance, features, reliability, suitability, service ability, endurance, aesthetics, image and reputation so that consumers can make the right purchasing decision by choosing Roof Lightweight Prima Truss.